PERANCANGAN BASEPLATE PELETAKAN PRODUK PADA MESIN TESTER PADA PT XYZ - Ahmad Haitami; hasibuan, Rizki (LPPM Universitas Putera Batam, 2022)
Product development in the industrial manufacture is currently at step growing up. All companies are required to take action for always do innovation and give a usefull new product. Design and development of a product is an important activity needed, because is related to make a functional product base on costumers needed. In a production process, one part of inverter component is often rejected with margin around 4,5% per day. The 3 cavity UHT Final tester machine is used to check the component whether the product is complete using the base plate already exist in each product size. The method is used in this research is Design For Manufacture and Assembly (DFMA). The result of calculation using reject product on work in shift 1st found 33 pcs reject products with success percentage rate of 95,42% and on shift 2nd found 40 pcs reject products with success percentage rate of 94,44%. The redesign of new base plate was then tested and got result 100% rate success on both shift, that’s mean there was decrease a 4,58% reject product on 1st shift and decrease 5,56% reject product on 2nd shift